Multimodale Therapie des Fibromyalgiesyndroms - Schiltenwolf, Marcus (Der Schmerz, 2017)
Background: The regular update of the guidelines on fibromyalgia syndrome, AWMF number 145/004, was scheduled for April 2017.MethodsThe guidelines were developed by 13 scientific societies and 2 patient self-help organizations coordinated by the German Pain Society. Working groups (n = 8) with a total of 42 members were formed balanced with respect to gender, medical expertise, position in the medical or scientific hierarchy and potential conflicts of interest. A search of the literature for systematic reviews on randomized controlled trials of multimodal therapy from December 2010 to May 2016 was performed in the Cochrane library, MEDLINE, PsycINFO and Scopus databases. Levels of evidence were assigned according to the classification system of the Oxford Centre for Evidence-Based Medicine version 2009. The strength of recommendations was achieved by multiple step formalized procedures to reach a consensus. Efficacy, risks, patient preferences and applicability of available therapies were weighed up against each other. The guidelines were reviewed and approved by the board of directors of the societies engaged in the development of the guidelines.Results and conclusionThe use of multimodal therapy (combination of aerobic exercise with at least one psychological therapy) with a duration of at least 24 h is strongly recommended for patients with severe forms of fibromyalgia.